NOVEL SECURITY MODEL USING DUAL SECURITY AND USER ROLES - Bhardwaj, Sukesh,; Yadav, Surendra, (International Journal of Psychosocial Rehabilitation, 2020)
Each and every organization has to manage users for the efficient functioning of the organization. Organizations have data that makes a relationship between users. In such an environment, data security is a major issue. For this type of issue, this paper proposes the dual security model involving the concept of using biometrics and pictures. The concept of authentication used is not only interactive but also secure and dynamic. It works together with the dual security, role assignment, and role-based access on the primary basis of the security model. The security analysis of the model using the online tools found the model to be very effective and promising.